Konsumsi Kompensasi pada Intensi Bermain dan Pembelian Gim Virtual - Anndy Tanuri; Stephen Timothy; Istijanto Istijanto; Prita Prasetya (Kajian Branding Indonesia, 2022)
The purpose of this research is to find out whether the consumption of compensation affects the intention to play and to buy virtual goods in context of the game Mobile Legends: Bang Bang. Researchers included the variables utility, self-indulgence, social interaction, and competitiveness to measure compensatory consumption indirectly. The data collection survey was conducted using an online judgmental sampling technique with the criteria of respondents being Mobile Legends: Bang Bang players aged 16 to 24 years living in Indonesia. SEM (Structural Equation Model) analysis using AMOS software was carried out on 292 samples obtained from online questionnaires using a judgmental sampling technique. The main findings in this study: (1) social interaction has a direct positive effect on the intention to buy virtual goods, (2) utility and self-indulgence are negative predictors of purchase intention, (3) the intention to play has a mediating effect on the effect of self-indulgence, interaction social media, and competitiveness towards purchase intentions of virtual goods.